Fabrication and Experimental Evaluation of Simple Tissue-Mimicking Phantoms with Realistic Electrical Properties for Impedance-Based Sensing - Liu, Jan; Goehring, Chris; Schiele, Frank; Moeller, Knut; Pott, Peter P. (International Journal of Integrated Engineering, 2021)
Venipuncture is one of the most often performed invasive clinical procedure. Nevertheless, complications still occur. One opportunity to counteract these complications is to indicate the insertion by electrical impedance measurement, which bases on the various electrical properties of different tissues. This paper presents the evaluation and reproducible fabrication of simple tissue-mimicking phantoms for investigation of impedance sensing techniques. Three different tissue-mimicking phantoms, representing blood, fat, and skin, were made on water-based recipes, including agar and gelatin as gelling agents. For evaluation of the electrical properties an electrode probe, made of hypodermic needles, was fabricated and characterized using six sodium chloride (NaCl) solutions of defined concentrations. For characterization of the phantoms, conductances were measured over a frequency range from 20 Hz up to 1 MHz using the self-fabricated electrodes. The calculated conductivities of the tissue-mimicking phantoms showed sufficient agreement with corresponding electrical literature data of native tissue. Tests with a layered tissue structure proved usability for impedance-based venous entry tests. However, the method proposed was not suitable for investigation of relative permittivity, which would be required for full electrical characterization.